HIV/AIDS, land-based livelihoods, and land reform in South Africa - Michael Aliber; Drimie, Scott; Kholadi Tlabela; Walker, Cherryl; Masika, Patrick; Mafu, Vuyo; Boltina, Sam; Khubeka, Bongi; Erskine, Sue; Quinlan, Tim; Wegerif, Marc; Manenzhe, Tshililo; et al. (International Food Policy Research Institute, 2006)
In 1994, South Africa’s Department of Land Affairs initiated a land reform programme. Land reform was—and still is—intended to redress the racial imbalance in landholding, develop the agricultural sector, and improve the livelihoods of the poor. However, there is now a growing concern that the propoor objectives of land reform may be under threat from the AIDS epidemic. Thus far there has been little tangible action aimed at either better understanding the relationship between land reform and the AIDS epidemic, or in respect of adjusting land reform policies and practice in reaction to the epidemic.